2021
DOI: 10.1007/s10557-021-07291-y
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Combined SGLT1/SGLT2 Inhibition in Reducing the Incidence of Stroke and Myocardial Infarction in Patients with Type 2 Diabetes Mellitus

Abstract: Purpose In patients with type 2 diabetes mellitus (T2DM), both sodium-glucose cotransporter 2 inhibitors (SGLT2is) and glucagon-like peptide receptor agonists (GLP-1 RAs) have demonstrated significant improvements in cardiovascular and kidney outcomes independent of their glycemic benefits. This paper will briefly compare the effect of SGLT2is and GLP-1 RAs to that of the SGLT1/2 inhibitor sotagliflozin on the incidence of myocardial infarction (MI) and stroke in patients with T2DM and further po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 49 publications
(83 reference statements)
1
14
0
Order By: Relevance
“…A network meta-analysis of 14 RCT, including the recent SCORED and SOLOIST trials investigating the effects of sotagliflozin, showed that among gliflozins, sotagliflozin had the greatest effect in lowering risk of stroke [ 27 ]. Thus, larger studies are needed to confirm the effects of SGLT1/SGLT2 inhibition on stroke in type 2 diabetes and to elucidate the potential mechanisms [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A network meta-analysis of 14 RCT, including the recent SCORED and SOLOIST trials investigating the effects of sotagliflozin, showed that among gliflozins, sotagliflozin had the greatest effect in lowering risk of stroke [ 27 ]. Thus, larger studies are needed to confirm the effects of SGLT1/SGLT2 inhibition on stroke in type 2 diabetes and to elucidate the potential mechanisms [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that dual SGLT-1 and SGLT-2 inhibition may give a clinical advantage, compared with GLP-1 RA and/or other SGLT-2i, in AMI patients. Indeed, it has been recently demonstrated that the relative increase in SGLT-1 inhibition with sotagliflozin is associated with a greater cardiovascular protection in patients with DM than the currently available SGLT-2i, that provide less degree of SGLT-1 inhibition [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although millet consumption was not able to increase the expression of this transporter in our study, recent research indicates that SGLT1 inhibition could be a therapeutic strategy for the management of diabetes, which can be associated with cardiomyopathy. In animal models with type 2 diabetes mellitus 29,[70][71][72] and clinical studies, 73,74 increased SGLT1 intestinal expression is observed in the small intestinal epithelium, which enhances the postprandial hyperglycaemia and its cardiovascular complications. Other studies with caco-2 cells indicate that the phytochemicals, such as polyphenols and tannins, have the capacity to suppress glucose uptake in intestinal cells, by the inhibition of SGLT1.…”
Section: Papermentioning
confidence: 99%